O-TS005. Significant effects on functional integration within the parietal memory network after high-frequency RTMS over the L-DLPFC in patients with Alzheimer’s disease - Liu, Xin; Yue, Houcang; Li, Yu-jun; Wang, Xiaoming (Clinical neurophysiology, 2021)
Introduction. High-frequency repetitive transcranial magnetic stimulation (rTMS) improves cognitive function in patients with Alzheimer's disease (AD), although the underlying mechanism is unclear. This study aimed to investigate the effects of rTMS treatment on brain networks in patients with AD using fMRI. Methods. Twenty-two patients with mild–to-moderate AD were recruited and randomly assigned to two groups matched for gender and age: the treatment group (TG,12 subjects), which received real therapy with 10 Hz rTMS over the left dorsolateral prefrontal cortex (L-DLPFC) for two weeks , and the sham control group (SG,10 patients), which received sham stimulation therapy. All patients were assessed using cognitive measurements and fMRI at baseline and after treatment. A data-driven method, functional connectivity density (FCD) mapping, was used to evaluate the effects of rTMS on the brain in patients with AD. Additional areas with significantly different FCDs were selected as seeds to calculate functional connectivity. Results. Compared with baseline values, TG showed significantly increased FCD in the bilateral precuneus (PCu), left inferior parietal gyrus (LIPG) and left triangular part of the inferior frontal gyrus (LIFG) after rTMS, but FCD in SG remained unchanged. The FCD in the left superior frontal gyrus (LSFG) significantly decreased in TG after rTMS. The bilateral PCu demonstrated increased FC with LSFG in TG. In addition, increased FC between RPCu and LIPG was also observed after treatment. TG also showed improved performance on MMSE and DST and NPI, ADL and ADAS-cog after treatment (p < 0.05). Conclusion. These findings demonstrated that 10 Hz rTMS over L-DLPFC had significant effects on functional integration within the parietal memory network (PMN) and its coupling with the site of stimulation in AD. The results suggest that rTMS can improve cognitive function in AD. Moreover, our study supported the usefulness of rTMS and functional connectivity as a potential measure to investigate brain networks in AD.